2019
DOI: 10.21203/rs.2.11999/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The predictive value of diaphragm ultrasound for weaning outcomes in critically ill children

Abstract: Background: Multiple studies have shown that diaphragmatic ultrasound can better predict the outcome of weaning in adults. However, there are few studies focusing on children, leading to a lack of sufficient clinical evidence for the application of diaphragmatic ultrasound in children. The purpose of this study was to investigate the predictive value of diaphragm ultrasound for weaning outcomes in critically ill children. Methods: Study included 50 cases whose mechanical ventilation(MV) time > 48 h, and all… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We could not find any difference in pre‐extubation DTF in children with successful extubation from failed extubation. Previously, a study in children reported DTF ≥ 21% as a predictor of successful extubation 4 . But a large multicentric adult study found no association of pre‐extubation DTF with extubation outcome 25 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We could not find any difference in pre‐extubation DTF in children with successful extubation from failed extubation. Previously, a study in children reported DTF ≥ 21% as a predictor of successful extubation 4 . But a large multicentric adult study found no association of pre‐extubation DTF with extubation outcome 25 .…”
Section: Discussionmentioning
confidence: 97%
“…In patients requiring thoracic surgery, muscle biopsies of the diaphragm and latissimus dorsi demonstrated a 35% reduction in force‐generating capacity of the diaphragm within 2 h of surgery but not latissimus dorsi 3 . Diaphragm being the major respiratory drive muscle, VIDD has an adverse impact on weaning off and is associated with prolonged mechanical ventilation and hospital stay 4 . Conventional measures of diaphragmatic function such as phrenic nerve conduction study, transdiaphragmatic pressure measurement, pulmonary function testing, fluoroscopy, and diaphragmatic electrical activity, have limitations such as the need for special equipment, invasiveness, and exposure to ionizing radiations 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that DTf less than 17% immediately postextubation was associated with extubation failure. Xue et al 15 in their study on 50 children who were ventilated for more than 48 hours found that DTf 21% was associated with successful extubation with a specificity of 0.81 and sensitivity of 0.82. Abdel Rahman et al 16 conducted a study on 106 children ventilated and showed that the best cutoff value of DTf for predicting weaning failure was 23.175% with an AUC of 0.932.…”
Section: Discussionmentioning
confidence: 96%
“…In one study, positive end‐expiratory pressure (PEEP) of 5 cmH 2 O was provided, while PEEP was not specified in the other study. In a cohort of 50 children, DTF was significantly higher in patients that were successfully extubated 45 . The optimal cutoff value associated with successful extubation was a DTF > 21%, with a positive predictive value of 94% and a negative predictive value of 56%.…”
Section: Weaning Of Mechanical Ventilationmentioning
confidence: 90%